(untitled) (Research, Society and Development, 2020)
The objective of the study was to characterize the mineral profile of Brazilian sweet potatoes and to evaluate the influence of cooking by immersion in water on these micronutrients. The cultivars Amorano, Júlia, Valentina, UGA 29, UGA 34, UGA 45, UGA 49, UGA 79, UGA 80 and UGA 81 were investigated. The levels of sodium, potassium, calcium, magnesium, phosphorus, iron, zinc, copper and silicon were quantified in the samples of raw and cooked sweet potatoes, which presented statistical difference between the varieties. The genotypes that stood out were Júlia and UGA 45 with higher mineral contents, while Amorano and UGA 29 were characterized by lower contents. Water immersion cooking reduced sodium, potassium and iron contents for all Brazilian sweet potato cultivars, while Zn, Mn and Cu showed the least changes. It is concluded that cooking in water significantly reduces the mineral content of most Brazilian sweet potato cultivars.